PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PRESTASI BELAJAR IPA SISWA SEKOLAH DASAR - Marlinda Mulu; Rikardus Dinar; Petrus Redy Partus Jaya (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2022)
The low of student learning outcomes and the limited activities of students in the classroom are often a learning problem to date. Therefore, it is very important to study the application of the PBL learning model and its effect on student achievement in elementary schools. The method used in this research is a quasi-experimental with pretest posttest design. The sample was selected randomly and divided into two groups, namely the control group without using the PBL model, while the experimental group using the PBL model. Furthermore, the research data were analyzed by independent sample t-test and one sample t-test. The results of data analysis showed that there was a significant difference between the control class and the experimental class. The PBL model is proven to be effective in increasing student achievement, this is indicated by the value of tcount 5, 209 t table 2,019, at 0.05. The assessment of the reference criteria for the KKM of subjects also shows that the average value of the experimental class has at least reached the KKM.